(RETRACTION) Indonesian Jurisprudence: Islamic Law Transformation In Law System Of Indonesia - Edwar, Ahmad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
This article has been retracted by Publisher based on the following reason:The Editor of Kordinat Journal found the double publications in the article publishing due to article's content similarity published in Analisis: Jurnal Studi Keislaman Vol 15, No. 2 (2015)URL: https://ejournal.radenintan.ac.id/index.php/analisis/article/view/730. Titled “FIQH KEINDONESIAAN: Transformasi Hukum Islam Dalam Sistem Tata Hukum Di Indonesia” with the author who is Chamim Tohari. Based on clarification, Author of the article have admitted that he has published the same article published in Analisis: Jurnal Studi Keislaman Vol 15, No. 2 (2015).One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.